Effect of Pulmonary Hypertension Severity on Graft Function and Quality of Life after Transplantation in Patients with End-Stage Renal Disease - susan Mohammadi-Kebar; Saeed Hoseininia; Afshan Sharghi; Elham yousefi-Ardabili (Patient Safety and Quality Improvement Journal)
Introduction:The present study aimed to assess the effect of pulmonary hypertension (PH) severity on the quality of life after transplantation in patients with end-stage renal disease (ESRD).Materials and Methods: In this cohort study, 60 ESRD patients who underwent kidney transplantation were followed for at least one year. Basic and laboratory findings were recorded in patients before and after transplantation. Quality of life was assessed by the 12-item health-related quality of life questionnaire (SF-12). The severity of PH was assessed based on pulmonary artery systolic pressure (PASP), and severe cases were excluded from the study. The obtained data were analyzed in SPSS software (version 24) using the chi-square test, independent t-test, and Pearson's correlation.Results: Based on the results, PH was observed in 83.3% of patients before transplantation. Following transplantation, there was a significant increase in quality of life and glomerular filtration rate (GFR) (P=0.001). Patients with PH had a lower quality of life before transplantation, as compared to those without PH (P= 0.009). Furthermore, the PASP level showed a significant positive relationship with the age of patients (r= 0.465; P<0.001) and the rate of improvement in quality of life after transplantation (r=0.288; P= 0.02).Conclusion: As evidenced by the results of this study, kidney transplantation improves kidney function and the quality of life of patients. The presence of PH leads to lower quality of life in ESRD patients before transplantation but has no effect on it after transplantation. Moreover, the severity of PH had no effect on the outcomes of a kidney transplant.